2021
DOI: 10.1099/ijsem.0.004938
|View full text |Cite
|
Sign up to set email alerts
|

Jinshanibacter allomyrinae sp. nov., isolated from larvae of Allomyrina dichotoma, proposal of Insectihabitans xujianqingii gen. nov., comb. nov. and emended descriptions of the genera Jinshanibacter, Limnobaculum and Pragia

Abstract: Taxonomic positions of four Gram-negative bacterial strains, which were isolated from larvae of two insects in Jeju, Republic of Korea, were determined by a polyphasic approach. Strains CWB-B4, CWB-B41 and CWB-B43 were recovered from larvae of Protaetia brevitarsis seulensis, whereas strain BWR-B9T was from larvae of Allomyrina dichotoma. All the isolates grew at 10–37 °C, at pH 5.0–9.0 and in the presence of 4 % (w/v) NaCl. The 16S rRNA gene phylogeny showed that the four isolates formed two distinct sublines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The morphologies of strains A18JL241 T and Y20 T were observed by scanning electron microscopy (Quanta 450, FEI), after incubation on 2216E solid medium at 28 °C for 5 days. Growth was tested at different temperatures (5,10,15,20,25,30,35,40, 45 and 50 °C) and pH (4.0-12.0, at intervals of 1.0 pH unit) in 2216E liquid medium. NaCl tolerance (0-8 %, at intervals of 1 %, w/v) was also tested using salt-free 2216E liquid medium as the basal medium.…”
Section: Physiology and Chemotaxonomymentioning
confidence: 99%
See 1 more Smart Citation
“…The morphologies of strains A18JL241 T and Y20 T were observed by scanning electron microscopy (Quanta 450, FEI), after incubation on 2216E solid medium at 28 °C for 5 days. Growth was tested at different temperatures (5,10,15,20,25,30,35,40, 45 and 50 °C) and pH (4.0-12.0, at intervals of 1.0 pH unit) in 2216E liquid medium. NaCl tolerance (0-8 %, at intervals of 1 %, w/v) was also tested using salt-free 2216E liquid medium as the basal medium.…”
Section: Physiology and Chemotaxonomymentioning
confidence: 99%
“…MK, menaquinone; PG, phosphatidylglycerol; DPG, diphosphatidylglycerol; PE, phosphatidylethanolamine; GL, unidentified glycolipids; PL, unidentified phospholipid; L, unidentified lipid. Data were from this study, except for cell morphology, menaquinones, polar lipids and DNA G+C contents of the reference strains[3,8,[35][36][37][38].…”
mentioning
confidence: 99%
“…The genus contains Gram-reaction-positive, catalase-positive, non-endospore-forming, motile or non-motile, rod-shaped bacteria and is monophyletic based on single or a few core genes [3, 4]. The phylogenomic relationship of the genus, based on core and whole genomes, has been partially studied for fewer than 50 species in the description of new taxa [5–12], However, Nouioui et al [5] showed that the genus is paraphyletic in phylogenetic analysis using whole genomes, with some species being transferred to the genus Thermomonospora . Recently, Lee et al [13] performed overall phylogenomic clustering of the genus based on core-genome analysis of nearly all the genomes available in public databases.…”
Section: Introductionmentioning
confidence: 99%
“…A few species have been recovered from the guts of the insects such as a termite, a mosquito and a wasp [14][15][16]. During our recent extensive study on bacterial strains isolated from larvae of an insect (Allomyrina dichotoma) using several media under anaerobic conditions, high diversity at the species level was shown to be present, leading to the discovery of a number of novel taxa of strains in addition to distinct strains [17]. In this study, we determine the taxonomic ranks of two isolates belonging to the family Enterococcaceae and propose two new species.…”
mentioning
confidence: 99%